Geophysical setting and urban form of a traditional city: examination of the Kurdish city of Sanandaj, Iran. Issue 6 (4th December 2019) - Alizadeh, Hooshmand; Bahrami, Bakhtiar; Farahani, Leila Mahmoudi
Abstract : Considering the nature of place which includes both inside and outside characteristics, as essential parts of existence, a city cannot be imagined without nature. Natural elements determine the character of urban form and they can be recognised as the primary components of the urban form configuration. Based on this leading point, the traditional city of Sanandaj, the capital of the Kurdistan province, located in the western part of Iran, is examined to reveal the nature of interaction between the city's urban form and its natural setting through time. Drawing on document analysis and observation of existing built form and its natural context, this paper highlights how the traditional city has been forming and changing through time. The results present evidences of how people related to nature and how the overall spatial principles of the city's traditional core were shaped on the basis of ideas stemming from the natural order while culture shapes the details of the place's structure.